Connecting Indonesia’s Maritime Cabotage and the 1982 United Nations Convention on the Law of the Sea - Kurniasari, Nilam Andalia (UI Scholars Hub, 2021)
On 7 May 2008, Indonesia enacted Law 17/ 2008 on Shipping (Shipping Act) which substituted Law 20/1992 on Shipping. In the new Shipping Act, maritime cabotage is scheduled to take its full effects on 7 May 2011, exactly three years after its enactment. By the scheduled time, domestic seaborne transportation in Indonesian territorial waters shall be carried out by Indonesian shipping companies, using Indonesian-flagged vessels manned by Indonesian citizens. As a result, foreign flagged vessels will be excluded from transporting goods and/or passengers between islands or ports within Indonesian territorial waters. Among the important reasons for the implementation of this principle are the sovereignty and protection of domestic shipping industry as well as Indonesia national security issues. This paper will argue that implementing maritime cabotage does not contradict any provisions in the 1982 UNCLOS. It will also show that maritime cabotage and the 1982 UNCLOS are closely related although this principle is not in the convention. The 1982 UNCLOS will advise Indonesia on the limit of its territorial waters, and thus where this largest archipelagic state in the world can exercise its maritime cabotage policy.